Remoção química de fósforo de efluente suinícola: implicações da qualidade do efluente sobre a eficiência do processo - Suzin, Lidimara (2016)
The swine production is one of the most important livestock activities in Brazil. On the other hand, it is also the main responsible for environmental impacts, which grow fast due to the high demand for animal protein. Thus, there is an increase on production concentration in smaller areas, which generates a large volume of manure with high concentration of nutrients, specially phosphorus and nitrogen. When the production of these effluents surpasses local demand to be used as fertilizers, if there are not well handled and treated, it may pose a threat to natural resources, to human and animal health. Furthermore, studies have already suggested a depletion of phosphorus sources, therefore, new strategies are needed for this nutrient recovery and reuse. Based on this context, in order to mitigate the two major issues involving phosphorus, the processes for its removal from swine wastewater have been widely studied. Chemical precipitation has gained greater attention due to its low cost, high efficiency and process speed. However, its application must be evaluated with regard to aspects involving the influence of effluent quality on the process and system efficiency in large scale. In this context, the present study aimed at evaluating the chemical removal of phosphorus from swine effluents treated by different nitrogen removal processes, using hydrated lime (Ca(OH)2) as a calcium source to precipitate Ca3(PO4)2 in bench scale and full-scale application.